Novel thiol-derivatized zinc(II) phthalocyanines - Garcia Vior, María Cecilia (2009)
Preparation and characterization of tetrasubstituted zinc(II) phthalocyanines in which sulfur is not linked to the macrocycle are reported herein for the first time. Thioacetic acid S-[3-(3,4-dicyano-phenoxy)-propyl]ester (4) was synthesized in 55% yield from 4-nitrophthalonitrile and thioacetic acid S-(3-hydroxy-propyl)ester (3). Tetrasusbtituted thiol-derivatized zinc(II) phthalocyanine 5 was obtained from 4 and zinc acetate in the presence of 1,8-diazabicyclo[5.4.0]undec-7-ene in butanol. Treatment of 5 with sodium methoxide afforded phthalocyanine 6.